1966
DOI: 10.1136/bmj.1.5491.834
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced Peripheral Neuropathy

Abstract: It has been thought that adult nervous tissues show a remarkable degree of resistance to injury by x rays. Clemedson and Nelson (1960), after a comprehensive review of the literature, state: " Nervous tissues, especially of adult animals, show a remarkable radio-resistance." In the past few years, however, experimental work on animals (Lander, 1959;Innes and Carsten, 1961) They were treated by a 4 MeV linear accelerator to an irregularly shaped field (Fig. 1) measuring approximately 15 by 5 cm., to include th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
1
4

Year Published

1972
1972
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(100 citation statements)
references
References 2 publications
3
92
1
4
Order By: Relevance
“…In an autopsy study of two patients with carcinoma of the breast who were suffering from brachial plexopathy after postoperative radiotherapy, marked fibrosis reportedly surrounded the nerve trunk with fibrous infiltration and replacement of nerve fibers. 19 This observation is compatible with the fact that the most frequently involved nerves in our study, namely, the hypoglossal nerve, the vagus nerve, and the recurrent laryngeal nerve, all pass through the neck region. Therefore, these nerves are prone to encroachment by fibrosis in the neck.…”
Section: Discussionsupporting
confidence: 91%
“…In an autopsy study of two patients with carcinoma of the breast who were suffering from brachial plexopathy after postoperative radiotherapy, marked fibrosis reportedly surrounded the nerve trunk with fibrous infiltration and replacement of nerve fibers. 19 This observation is compatible with the fact that the most frequently involved nerves in our study, namely, the hypoglossal nerve, the vagus nerve, and the recurrent laryngeal nerve, all pass through the neck region. Therefore, these nerves are prone to encroachment by fibrosis in the neck.…”
Section: Discussionsupporting
confidence: 91%
“…It can be used as an example of how the incidence of late effects can be drastically increased by changes of the treatment parameters. The relation between the treatment schedule and BPL has been studied by several investigators (11,(16)(17)(18)(19)(20)(21). In a classic paper, Stoll & Andrews (16) found symptoms of brachial plexus neuropathy in 73% of patients who had been treated with approximately 55 Gy in the plexus but only in 15% if the dose was 51 Gy.…”
Section: Complications From the Arm And Shouldermentioning
confidence: 99%
“…In patients who received the total dose over 60 Gy, the signs and symptoms of plexopathy appeared during the first year post therapy, while in those who were received less than 60 Gy, the interval exceeded one year. Stoll et al and Bentzen et al [16,17] found that the interval between radiotherapy and the beginning of RIBP depends on the total dose and the dose per fraction. This interval becomes shorter when dose per fraction and/or total dose increases.…”
mentioning
confidence: 99%
“…Earlier reports described brachial plexus damage with high fraction doses-more than 4 Gy (Table I). Stoll et al [16] diagnosed RIBP in 73% and 15% of patients, who were treated by a 4 MV photons with a total dose of 55 Gy in 4.58 Gy per fraction and 51 Gy in 4.25 Gy per fraction to the brachial plexus accordingly. Patients were treated with one field to the supraclavicular lymph node region after total mastectomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation